Learning Design Utilizing Discord Platform and Jigsaw Strategy to Effectively Enhance Students’ Listening Skills - Ramadhan, Iqbal; Kartika Degeng, Made Duanda; Praherdhiono, Hendry (Journal of Educational Management and Strategy, 2025)
The advancement of digital communication platforms has transformed the landscape of language learning, providing new opportunities for interactive and collaborative instruction. This study aims to describe the learning design that utilizes the Discord platform integrated with the Jigsaw strategy to enhance students’ listening skills in English language learning. The research was conducted within the Postgraduate Program in Learning Technology at the State University of Malang. The background of this study lies in the need to create engaging and student-centered learning environments that improve active participation and comprehension in listening activities. This study employs a descriptive qualitative approach with data collection methods including observation, interviews, and documentation. The findings indicate that the combination of Discord and the Jigsaw strategy encourages effective communication, peer collaboration, and contextual learning experiences. Students actively participate in group discussions, share comprehension results, and practice listening in authentic digital environments. Moreover, the integration of Discord facilitates flexibility and interaction beyond the classroom, allowing continuous feedback and monitoring by instructors. The implementation of this design successfully enhances students’ listening comprehension, motivation, and digital literacy. Overall, the study demonstrates that integrating collaborative digital platforms such as Discord with cooperative learning strategies like Jigsaw can significantly improve language learning outcomes in higher education contexts.